Current global trends and prospects for research in beach volleyball: An analytical review of the scientific literature - Hrynchenko, Ihor; Sobko, Iryna; Tiurin, Illia (Educational Challenges, 2025)
The study of beach volleyball, a dynamic and rapidly evolving sport, is gaining increasing relevance, particularly in the context of intensifying international competition. As the global standard of play continues to rise, the scientific foundations of training are becoming a crucial factor in achieving high athletic performance. This is especially pertinent for Ukraine, where beach volleyball holds significant potential for further development. This study aims to identify and systematize key directions and trends in contemporary scientific research on beach volleyball, as well as to outline its prospects for advancement in Ukraine. The research methodology is based on a comprehensive analysis of scientific literature, incorporating classification, systematization, interpretation, and generalization. Results: the analysis of 28 relevant studies has revealed several significant trends in beach volleyball research. Notably, physical attributes such as jumping ability, explosive power, and speed are critical determinants of competitive success. High performance is closely linked to the effectiveness of offensive and defensive strategies, with tactical interactions and adaptability to game dynamics playing essential roles. Additionally, the individualization of training programs – tailored to players’ specific roles and age-related characteristics – emerges as a key factor in optimizing performance. In conclusion, the findings underscore the importance of specialized physical preparation and highlight the impact of a player’s position on physical exertion. Based on these insights, practical recommendations have been formulated for coaches, researchers, and sports organizations involved in the training and development of beach volleyball athletes in Ukraine.